POLITIK DAN DEMOKRASI DALAM PENYUSUNAN PERENCANAAN NASIONAL - Dicky Rezady Munaf (Jurnal Sosioteknologi, 2009)
The arrangement of National Development Plan are fully related to the political and democracy mechanism which grows among people. Basically this must be flexible so can adapt to the changes that happen all the time and in different situation. On the other hand, this must be able to develop all level potencies from the smallest community to the central government and must be able to realize the good government. There are three steps to understand in arranging the National Development Plan: planning, realization, and supervision. Indonesia experienced evolution of National Development Plan in four government period . The result of the development in each government significantly is not quite different because they used dissimilar parameter. Democracy which is formed from good and honest political system that put national interest over individual interest can create good Balance of power. Key words : The arrangement of National Development Plan, democracy, politic.